The meaning of sport and physical activity from a youth perspective - Rizqie Windiyarto Rizqie; Fajar Ari Widiyatmoko; Osa Maliki (Sriwijaya Journal of Sport, 2025)
Research Problems: Young people's understanding of the meaning of sport and physical activity is important to research as it contributes to improving health, well-being, and nation-building, especially in Indonesia's demographic bonus era. Research Objectives: This research aims to explore the youth's understanding of Semarang City's meaning of sport and physical activity. Methods: This study uses a qualitative phenomenological approach with data collection methods through in-depth interviews using purposive sampling with 18 informants aged 15-29 who are active in sports in Semarang City. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. Results: The results showed that physiological needs are still the main needs to maintain health, increase metabolism, and optimise body functions. Conclusion: This research shows differences with previous studies that emphasise security and social needs, but this research reveals more that physiological needs remain the main motivation. However, aspects such as well-being and refreshing also emerged as important factors, detailing that sport and physical activity were also seen to occupy leisure time, cope with stress, and improve mood. Further research is recommended to explore the influence of security and social needs in sports and physical activity motivations.